A metric stability result for the very strict CD condition. (September 2022) - Magnabosco, Mattia
Abstract: Schultz (2018) generalized the work of Rajala and Sturm (2014), proving that a weak non-branching condition holds in the more general setting of very strict CD spaces. Anyway, similar to what happens for the strong CD condition, the very strict CD condition seems not to be stable with respect to the measured Gromov Hausdorff convergence (cf. Magnabosco, 2022). In this article I prove a stability result for the very strict CD condition, assuming some metric requirements on the converging sequence and on the limit space. The proof relies on the notions of consistent geodesic flow and consistent plan selection, which allow to treat separately the static and the dynamic part of a Wasserstein geodesic. As an application, I prove that the metric measure space R N equipped with a crystalline norm and with the Lebesgue measure satisfies the very strict CD ( 0, ∞ ) condition.